Correlation between Histological Activity and Endoscopic, Clinical, and Serologic Activities in Patients with Ulcerative Colitis - Dae Bum Kim; Kang-Moon Lee; Ji Min Lee; Yoon Yung Chung; Hea Jung Sung; Chang Nyol Paik; Woo Chul Chung; Ji-Han Jung; Hyun Joo Choi (Gastroenterology Research and Practice)
Objectives. Recent studies suggest that histological healing is a treatment goal in ulcerative colitis (UC). We aimed to evaluate the correlation between histological activity and clinical, endoscopic, and serologic activities in patients with UC. Methods. We retrospectively reviewed medical records from patients with UC who underwent colonoscopy or sigmoidoscopy with biopsies. The Mayo endoscopic subscore was used to assess endoscopic activity. Biopsy specimens were reviewed by two blinded pathologists and scored using the Geboes scoring system. Results. We analyzed 154 biopsy specimens from 82 patients with UC. Histological scores exhibited strong correlation with endoscopic subscores (Spearman’s rank correlation coefficient r=0.774, p<0.001) and moderate correlation with C-reactive protein levels (r=0.422, p<0.001) and partial Mayo scores (r=0.403, p<0.001). Active histological inflammation (Geboes score ≥ 3.1) was observed in 6% (2 of 33) of the endoscopically normal mucosa samples, 66% (19 of 29) of mild disease samples, and 98% (90 of 92) of moderate-to-severe disease samples. Conclusions. Histological activity was closely correlated with the endoscopic, clinical, and serologic UC activities. However, several patients with mild or normal endoscopic findings exhibited histological evidence of inflammation. Therefore, histological assessment may be helpful in evaluating treatment outcomes and determining follow-up strategies.